2014
DOI: 10.1044/2014_ajslp-13-0038
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Language Input to Children Enhances Learning in a Treatment Context

Abstract: The results support the use of highly variable input in a therapeutic context to facilitate grammatical morpheme learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(101 citation statements)
references
References 38 publications
4
95
0
1
Order By: Relevance
“…In language learning, children and adults learn non-adjacent dependencies (between A and B in AXB) only when there are many intervening items (X's; Gómez, 2002). Children with Specific Language Impairment learn real-language non-adjacencies (e.g., is VERB-ing, as in "is jumping") better when multiple word types are used in teaching (Plante et al, 2014).…”
Section: What Can Acoustic Variability Tell Us About the Nature Of Inmentioning
confidence: 99%
“…In language learning, children and adults learn non-adjacent dependencies (between A and B in AXB) only when there are many intervening items (X's; Gómez, 2002). Children with Specific Language Impairment learn real-language non-adjacencies (e.g., is VERB-ing, as in "is jumping") better when multiple word types are used in teaching (Plante et al, 2014).…”
Section: What Can Acoustic Variability Tell Us About the Nature Of Inmentioning
confidence: 99%
“…This was one of the reasons why the current study presented each string of syllables four times only. Comparing to previous studies which found successful generalization in children with language impairments (Plante et al, 2014) However, the 18-month-old infants in Gómez (2002) could discriminate the trained and untrained non-adjacent dependencies with only one presentation in the training phase.…”
Section: Discussionmentioning
confidence: 87%
“…High variability was also found to be important for atypically developing individuals in learning different grammatical structures (Plante et al, 2014;von Koss Torkildsen, Dailey, Aguilar, Gómez, & Plante, 2013) and for typically developing adults in learning noun gender subcategories in a foreign language (Eidsvåg, Austad, Plante, & Asbjørnsen, 2015). All these studies suggest a link between statistical learning and language acquisition and disorders although longitudinal evidence is still warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations